The Aesthetics Of Conflict In The Creation Of The Film Salisiah Adaik - Ferdinand Almi; Sahrul N; Fajar Indayani (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study examines the aesthetics of conflict in the creation of the film Salisiah Adaik, which portrays a dispute between two Minangkabau marriage customs: the Bajapuik tradition of the Pariaman community and the Maisi Sasuduik tradition of the Payakumbuh community. The research aims to explore how conflict is constructed not only as a dramatic element but also as a form of Minangkabau cultural aesthetics. The study employs a qualitative approach using narrative and film aesthetic analysis. The analysis focuses on character development, the use of local dialects, the structure of customary conflict, and cinematic elements such as art direction, lighting, and traditional music. The findings reveal that the aesthetics of conflict in the film are constructed through linguistic differences, customary disputes, and visual and auditory approaches that strengthen the dramatic quality of the narrative. The conflict in the film also reflects the Minangkabau philosophy, “basilang kayu dalam tungku, mako api ka hiduik” (crossed firewood in the stove keeps the fire alive), which views disagreement as a process leading to consensus. Therefore, conflict in Salisiah Adaik functions not only as a driving force of the narrative but also as a representation of Minangkabau cultural aesthetics.